Analysis of the thermal physiology of the Andean lizard Stenocercus festae (Squamata: Iguanidae: Tropidurinae) to predict possible extinctions in their populations due to climate change - Guerra Correa, Estefany Sofía (PUCE, 2016)
We studied the thermal physiology of the Andean lizard Stenocercus festae, a thermoregulatory lizard that inhabits sub-Andean forests at southern Ecuador, to address the potential effects of climate change on its populations. Experimental data showed that the preferred body temperature (Tpref) was 21.79 C, the minimum critical thermal (CTmin) was 6.20 C, and the maximum critical thermal (CTmax) was 46.24 C. We applied the model for thermoregulatory lizards proposed by Sinervo et al. (2010) that integrates georeferenced points of species distribution, the Tpref obtained in the field, the lowest temperature at which lizards are active (Tact), the operative temperature (Te), and daily maximum air temperature to get the number of hours of restriction (Hr, the number of hours per day when Te exceeded Tpref) and hours of activity (Because this model was not suitable for this species, we modified it by proposing three different scenarios of Tpref and Tact values, as well as by changing the way we predict extinctions from restriction hours. Both modifications predicted that on 2010, 13.8% of the populations had already gone extinct, including the population of study; by 2020, 60% of the populations that went extinct in 2010 will probably recover by recolonization. Warming tolerance (WT), compared with a closely related species, showed that S. festae tolerates higher temperatures than S. guentheri because it presents a wider difference between its CTmax and the average and maximum Tair, as well as a wider thermal tolerance breadth.